Constitutionalism and Democratic Governance in Africa: Contemporary Perspectives from Sub-Saharan Africa - Morris Kiwinda Mbondenyi (Pretoria University Law Press (PULP), 2013)
About the publication Adieu, Steve: Tribute to a scholar of African constitutionalism This volume of essays on constitutionalism in Africa is devoted to the memory of Steve Odero Ouma, who spent most of his professional life working on these issues. He was a colleague and friend to many of the contributors to this volume, and no doubt to many of its actual and potential readers. Steve passed away on 23 February 2012. This publication is a collection of essays written mainly by graduates of the Master's Programme in Human Rights and Democratisation in Africa. (One of the authors, Mwiza Jo Nkatha was one of Steve's class mates in 2005.) The only exception, Professor Kofi Quashigah, is the Dean of the Faculty of Law, University of Ghana, at Legon, Accra. My sincere thanks and congratulations go to each of these contributors for their pointed and important contributions to this volume. I should mention here that the University of Ghana is one of the twelve partner universities in the programme. The other partner faculties are: the University of the Western Cape (South Africa); the University of Venda (South Africa); Makerere University, Uganda; the University of Ghana, Ghana; the University of Lagos, Nigeria; Université Gaston Berger, Senegal; the University of Abomey Calavi, Benin; Catholic University of Central Africa, Cameroon; Universidade Eduardo Mondlane, Mozambique; Addis Ababa University, Ethiopia; University of Mauritius, Mauritius; and American University, Cairo, Egypt. The editors are two prominent Kenyan academics, Dr Morris Kiwinda Mbondenyi, Senior Lecturer in Law, Africa Nazarene University and Professor Tom Ojienda, Associate Professor of Law, Moi University. I would like to thank them, in particular, for their hard work and dedication in bringing this work into being. They oversaw the peer-review process, and worked with individual authors. It should certainly also be mentioned that Steve Odero conceived of and initiated the idea of this book, together with the two editors, and walked some distance on the road towards this publication. Sadly, it was a road not completed, due to Steve's sudden death. I am sure Steve would have wanted these pages to take us all along a journey he embarked on, but could not complete: the unfinished journey to secure genuine constitutionalism in states across Africa. Frans Viljoen Director, Centre for Human Rights About the editors: Dr. Morris Kiwinda Mbondenyi is a Senior Lecturer in Law and the Head of the Africa Nazarene University Law School, Kenya. Tom Ojienda is Associate Professor of Law at Moi University, Kenya.